Penerapan Inquiry Based Learning dengan Teknik World Café dalam Pembelajaran PAI di Sekolah Dasar - Wahyuni, Nur; Fachrudin Yusuf, Wiwin; Yusuf, Achmad (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to describe the implementation of the Inquiry Based Learning (IBL) model using the World Café technique in Islamic Religious Education (PAI) learning at SDN Kedungcangkring Jabon, Sidoarjo. The research was motivated by the low level of student engagement and learning interest in PAI, which has largely been dominated by the lecture method. This research employed a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The data were analyzed through reduction, presentation, and conclusion drawing. The findings indicate that the application of IBL with the World Café technique creates a more active, participatory, and collaborative classroom atmosphere. Students are directly involved in the process of knowledge construction through group discussions, idea rotation, presentations, and peer-to-peer knowledge exchange. The innovation not only improves students’ understanding of the subject matter but also enhances 21st-century skills such as critical thinking, communication, teamwork, and creativity. Several challenges were identified, including time limitations, heterogeneous student abilities, and insufficient initial readiness. However, these obstacles can be addressed through careful planning, intensive guidance, and continuous teacher facilitation. Thus, the application of IBL with the World Café technique has proven effective in improving the quality of Islamic Religious Education learning in elementary schools.